2006
DOI: 10.1097/01.mcg.0000225672.68852.05
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Usefulness of 18-Fluorodeoxyglucose Positron Emission Tomography in the Differential Diagnosis, Staging, and Response Evaluation After Concurrent Chemoradiotherapy for Pancreatic Cancer

Abstract: FDG-PET is a very useful tool in diagnosing pancreatic cancer. FDG-PET may be also used as an adjunct for determining the treatment modality of pancreatic cancer and evaluating tumor response to chemoradiation therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
74
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(79 citation statements)
references
References 28 publications
3
74
0
2
Order By: Relevance
“…Our previous report demonstrated that initial stages using CT scan were changed in 26.9% patients with pancreatic cancer after PET scan (Bang et al, 2006a). Positron emission tomography scans showed high sensitivity and specificity in detecting metastatic disease, including liver, lungs, and peritoneum (Pakzad et al, 2006;Bang et al, 2006a).…”
Section: Discussionmentioning
confidence: 98%
“…Our previous report demonstrated that initial stages using CT scan were changed in 26.9% patients with pancreatic cancer after PET scan (Bang et al, 2006a). Positron emission tomography scans showed high sensitivity and specificity in detecting metastatic disease, including liver, lungs, and peritoneum (Pakzad et al, 2006;Bang et al, 2006a).…”
Section: Discussionmentioning
confidence: 98%
“…Therefore, although in staging FDG-PET did not perform precisely enough except for detecting bone metastases, by evaluating the SUV, FDG-PET may provide such additional information on the biological aggressiveness of the tumor, and thus play an important role in helping to select patients for subsequent surgical therapy. Some small studies reported that the tumor SUVs were useful in predicting the effectiveness of chemotherapy for unresectable pancreatic cancer [17,26,27] . However, conclusions must await further studies including larger population of patients.…”
Section: The Role Of Fdg-pet In Staging Of the Diseasementioning
confidence: 99%
“…It has been said that one possible reason for the apparent low sensitivity of FDG-PET is the close proximity of the peripancreatic and paraaortic lymph node basins to the primary tumor, which can obscure their detection [2,16] . The important impact of FDG-PET on staging has been in its ability to identify distant metastases [17] . According to the previous reports [18] , the sensitivity of FDG-PET for detecting hepatic metastases is about 70%, while that of this study was 52.6%.…”
Section: The Role Of Fdg-pet In Staging Of the Diseasementioning
confidence: 99%
“…Considering the high frequency of advanced and potentially systemic disease at the time of initial diagnosis of pancreatic cancer, 19 preoperative prediction of early recurrence and aggressive biologic behavior of tumor can inform the prognosis and help patients avoid unnecessary surgery. It was hypothesized that PET parameters could reflect not only tumor burden, but also tumor biology, because 18F-FDG uptake correlates with cellular proliferation 20,21 and tumor behavior 6,7,22,45 in pancreatic cancer. According to our results, preoperative volume-based PET parameters MTV 2.5 and TLG were found to represent some tumor biologic characteristics in resected pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, PET has been shown to provide several important clinical information about pancreatic cancer in terms of differential diagnosis between benign and malignant neoplasms, 1,2 preoperative staging, 3,4 the evaluation of therapeutic response, 5,6 and the prediction of prognosis. 7,8 Fluorine-18 fluorodeoxyglucose ( 18 F-FDG) is metabolized similarly to glucose in tumor cells, which is transported into a cytoplasm through specific glucose transporters in cell membrane and phosphorylated by hexokinase.…”
Section: Introductionmentioning
confidence: 99%